Oxygen isotopes suggest elevated thermometabolism within multiple Permo-Triassic therapsid clades - Kévin Rey; Romain Amiot; François Fourel; Fernando Abdala; Frédéric Fluteau; Nour-Eddine Jalil; Jun Liu; Bruce S Rubidge; Roger MH Smith; J Sébastien Steyer; Pia A Viglietti; Xu Wang; et al. (eLife, 2017)
The only true living endothermic vertebrates are birds and mammals, which produce and regulate their internal temperature quite independently from their surroundings. For mammal ancestors, anatomical clues suggest that endothermy originated during the Permian or Triassic. Here we investigate the origin of mammalian thermoregulation by analysing apatite stable oxygen isotope compositions (δ18Op) of some of their Permo-Triassic therapsid relatives. Comparing of the δ18Op values of therapsid bone and tooth apatites to those of co-existing non-therapsid tetrapods, demonstrates different body temperatures and thermoregulatory strategies. It is proposed that cynodonts and dicynodonts independently acquired constant elevated thermometabolism, respectively within the Eucynodontia and Lystrosauridae + Kannemeyeriiformes clades. We conclude that mammalian endothermy originated in the Epicynodontia during the middle-late Permian. Major global climatic and environmental fluctuations were the most likely selective pressures on the success of such elevated thermometabolism.